2021
DOI: 10.1111/jocd.13965
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of skin moisturization with hyperharmonized hydroxyl modified fullerene substance

Abstract: Background Hyper Harmonized Hydroxyl Modified Fullerene Substance (3HFWC+) establishes hydrogen bonds with the surrounding water molecules and organizes them in clusters with the liquid crystalline state, similar to the properties of water surrounding the biomolecules. Aims To investigate the moisturizing properties of hyperharmonized fullerenol—3HFWC+ as an emulsion O/W ingredient on the skin. Patients/Methods We have analyzed the reflexion of the blue light from the skin, in vivo, with different levels of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…On the other hand, there is wide range of fullerene-based skincare products that have been clinically verified and used by people for several years, implying that fullerenes and related materials are quite safe for topical application [ 81 ]. Compared to the control groups, cosmetic products containing 3HFWC nanosubstance demonstrated positive effects, including faster collagen regeneration and prompt skin reaction to the negative environmental influences [ 13 , 82 ]. The in vitro studies with melanoma cells recently revealed that 3HFWC nanosubstance treatments induced cell reprogramming, suggesting their use as a nonaggressive strategy for tumor growth suppression [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is wide range of fullerene-based skincare products that have been clinically verified and used by people for several years, implying that fullerenes and related materials are quite safe for topical application [ 81 ]. Compared to the control groups, cosmetic products containing 3HFWC nanosubstance demonstrated positive effects, including faster collagen regeneration and prompt skin reaction to the negative environmental influences [ 13 , 82 ]. The in vitro studies with melanoma cells recently revealed that 3HFWC nanosubstance treatments induced cell reprogramming, suggesting their use as a nonaggressive strategy for tumor growth suppression [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fullerenes (or buckyballs) are spherical structures with many carbon atoms [ 260 ]. They can deliver biopeptides in cosmetics (e.g., anti-wrinkle, anti-acne, lightening toner, pore reduction, and moisturizing creams) and sunscreen [ 261 , 262 ].…”
Section: Peptide Delivery Systemsmentioning
confidence: 99%
“…So that it has been widely studied in cosmetic materials, biomedicine, and other aspects. In the field of skin care, fullerenes have the functions of antioxygen, 8 anti‐wrinkle, 9,10 whitening, 11 protective barrier, anti‐inflammatory, acne removal, rad fading, 12 shrinking pores, and so on. In addition, the scientists have found that fullerenes have excellent therapeutic effects on parkinson's disease, 13,14 enteritis, 15 diabetes, pulmonary fibrosis, 16 and reduced side effects in the process of radiotherapy and chemotherapy significantly 17 …”
Section: Introductionmentioning
confidence: 99%